Avaliação da atenção primária à saúde nas ações de controle da hanseníase no município de Betim, Minas Gerais - Nayara Figueiredo Vieira (2015)
Leprosy is currently considered one of the neglected tropical diseases to be infectious-contagious, with crippling power and directly related to poverty. In epidemiological terms, in Brazil, leprosy is still considered a public health problem. Therefore, strategies such as decentralization of leprosy control actions to the scope of primary care services have been incorporated. Thus, leprosy became a strategic specialization of operation of the PHC services in the Brazilian territory, being necessary to evaluate the performance of primary care services in the care of leprosy. Objective: Analyze the performance of primary health care services in leprosy control actions and characterize the epidemiological behavior of the disease in the municipality of Betim. Method: This is an evaluative research, carried out in two steps. The first stage, health professionals (doctors and nurses) were interviewed in the city of Betim, as well as community health workers, managers and users of primary care. An assessment tool that measures the degree of orientation of primary care in the performance of leprosy control actions was used, and referred to the attributes of primary care (access, gateway, completeness of services available, completeness of services performed, coordination, career counseling, family counseling and community orientation). In the second stage, leprosy indicators were calculated recommended by the Ministry of Health and new ones created for this study. It was constructed a historical series from 2003 to 2013, to evaluate the endemic behavior in the city of Betim and used as source, the Information System for Notifiable Diseases. Results: From the result of the first stage of this study, it can be observed a high level of orientation of primary health care in leprosy control actions for following attributes: gateway, completeness of services, completeness of services, continuing care, coordination and family counseling from the perspective of different key informants interviewed. However, it was noted a weakness in access, community orientation and vocational guidance with poor orientation of primary care in leprosy control actions. The construction of the assistance flowchart of the leprosy user identified the complexity of the health care in Betim, and that the leprosy referral service is responsible for the coordination of care. In the second stage of the study, there was a decreasing trend in the detection of new cases of leprosy 2003 to 2007, though increasing in detecting the last six years of the time series (2008-2013). There was a high proportion of new cases being diagnosed with grade 2 disability. As for the operational quality indicators instability was observed in the parameters regarding the cure rate and the proportion between the contacts examined recorded. The detection of cases occur predominantly by routing and spontaneous demand. In relation to the notification of leprosy cases in the primary health care service, it was observed a decline. This fact was also observed when assessed the proportion of cases treated in the primary care service. Conclusion: It is concluded from this study that the Betim city had average performance for leprosy control actions within primary care, since, from the perspective of key informants there weaknesses regarding the access and the community and professional guidance, impacting the quality of care provided in the care of leprosy. In addition, regarding the operational indicators that portray the quality of care offered to users of leprosy service, was obtained nonlinear parameters when analyzing the historical series highlighting irregularities in the provision of good quality services.